The Role of Work-Life Balance and Employee Satisfaction to Give Commitment to The Company Literature Review - Erna Herlina; Widodo Sunaryo; Slamet Sutrisno; Junengsih Junengsih; Nanda Hidayati (Budapest International Research and Critics University, 2022)
Developments that occur within the company require the role of employees in order to help improve company performance. In this development, it is necessary to have a commitment given by employees to the company. Of course, it is necessary to have a factor that can affect the commitment shown by employees, namely through the work-life balance and the satisfaction felt by the employees. The method used by the researcher is a systematic literature review that focuses on work life balance, job satisfaction and commitment. The results prove that the role of work-life balance and the satisfaction felt by employees are able to shape the desire of employees to give their commitment. The role of work-life balance and job satisfaction can affect organizational commitment. The commitment given by employees must be based on satisfaction in order to form high loyalty behavior. The more satisfied the employee, the more committed the employee will be to the company.